2017
DOI: 10.1016/j.coche.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Advances and trends in two-zone fluidized-bed reactors

Abstract: Two-zone fluidized bed reactors, devices to carry on two reactions in a single reactor, have been widely studied in our group. This work summarizes the developments achieved after a previous review published in 2005 and shows how this technology can be applied in a wide variety of reactions. The advantages for each kind of process are discussed, as well as several proposals for improvement of the reactor aimed to achieve new functions or to improve the process performance. Finally, the possibilities of this ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Our group has found that the use of a two-zone fluidized bed reactor can counteract the catalyst deactivation, by (1) CH 4 + CO 2 ↔ 2H 2 + 2CO providing simultaneous reaction and regeneration in a single vessel [10]. In order to simulate this reactor and to search for the optimal operation conditions, a good knowledge of the process kinetics is needed, including also the catalyst deactivation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has found that the use of a two-zone fluidized bed reactor can counteract the catalyst deactivation, by (1) CH 4 + CO 2 ↔ 2H 2 + 2CO providing simultaneous reaction and regeneration in a single vessel [10]. In order to simulate this reactor and to search for the optimal operation conditions, a good knowledge of the process kinetics is needed, including also the catalyst deactivation kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with all these disadvantages (i to iii), a two-zone fluidized bed reactor (TZFBR) has been proposed to carry out the MDR, allowing in this way the simultaneous catalyst regeneration in a single unit. In the non-conventional TZFBR reacting system [16,17], due to its design, both processes can be carried out simultaneously: the catalytic dry reforming reaction in the upper zone of the bed, and the regeneration of the catalyst in the lower zone. The formation of two zones is achieved by feeding the The TZFBR+MB configuration, thanks to the simultaneous regeneration, may provide a steady state operation in conditions where a conventional fluidized bed membrane reactor would usually suffer deactivation by coking (e.g., , [18,19]).…”
Section: Introductionmentioning
confidence: 99%
“…The Two Zone Fluidized Bed Reactor (TZFBR) is an effective way to counteract the effects of catalyst deactivation, as several previous studies have proved in a variety of reactions (Herguido et al, 2005;Herguido and Menéndez, 2017). In this type of reactor, two zones are created in a fluidized bed by the simple procedure of feeding into the hydrocarbon stream at an intermediate point of the bed and placing an oxidizing stream at the bottom of the reactor.…”
Section: Introductionmentioning
confidence: 99%